Repeated eccentric exercise bouts do not exacerbate muscle damage and repair - Nosaka, K.; Newton, M. (The Journal of Strength and Conditioning Research, 2002)
This study examined whether performing repeated bouts of eccentric exercise 2 and 4 days after an initial damaging bout would exacerbate muscle damage. One arm performed 3 sets of 10 eccentric actions of the elbow flexors (ECC1) using a dumbbell set at 50% of the maximal isometric force at 90° (SINGLE). Two weeks later the same exercise was performed by the opposite arm with the exception that subsequent bouts were performed 2 (ECC2) and 4 (ECC3) days after ECC1 (REPEATED). In the REPEATED condition, maximal isometric force (MIF) decreased to the same level immediately after ECC1-3, and the decreases in range of motion (ROM) and increases in upper arm circumference immediately postexercise were similar among the bouts. However, no significant differences in changes in MIF, ROM, muscle soreness, and plasma creatine kinase activity were evident between the SINGLE and REPEATED conditions when excluding the changes immediately after ECC2 and ECC3. These results suggest that ECC2 and ECC3 did not exacerbate muscle damage or affect the recovery process.